2016
DOI: 10.3390/atmos7110148
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Drying and Rewetting on CO2 and CH4 Emissions from High-Altitude Peatlands on the Tibetan Plateau

Abstract: This study used mesocosms to examine the effects of alternate drying and rewetting on CO 2 and CH 4 emissions from high-altitude peatlands on the Tibetan Plateau. The drying and rewetting experiment conducted in this study included three phases: a 10-day predrying phase, a 32-day drying phase, and an 18-day rewetting phase. During the experiment, the water table varied between 0 and 50 cm with respect to the reference peat column where the water table stayed constant at 0 cm. The study found that drying and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Wetlands have relatively high SOC concentration, and its anaerobic environment is favorable for methanogens [ 39 ], resulting in large emissions of CH 4 . While the decline of water table in drying phase during DWC treatment caused a reduction of CH 4 emissions [ 22 ]. The effects of DWC on N 2 O emissions were only significant in forests soils, which may be attributed to the thicker organic layer that has higher SOM concentrations compared with other ecosystem types, which plays an important role in resisting the repeated stress of changes in water moisture because of the hydrophobic property of SOM [ 16 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wetlands have relatively high SOC concentration, and its anaerobic environment is favorable for methanogens [ 39 ], resulting in large emissions of CH 4 . While the decline of water table in drying phase during DWC treatment caused a reduction of CH 4 emissions [ 22 ]. The effects of DWC on N 2 O emissions were only significant in forests soils, which may be attributed to the thicker organic layer that has higher SOM concentrations compared with other ecosystem types, which plays an important role in resisting the repeated stress of changes in water moisture because of the hydrophobic property of SOM [ 16 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the effect of DWC in the same ecosystem type can have divergent effects on different GHGs. For instance, CO 2 emissions significantly increased but N 2 O emissions decreased after two times of DWC in grassland soils, likely because a constant moisture of soils can positively affected N 2 O emissions and repeated DWC may affect the activities of microorganisms [ 21 ], while DWC was observed to significantly decrease CH 4 emissions but do not affect CO 2 emissions in wetlands soils [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies observed that rewetting of drained peatland stimulates CO 2 -C sink functions immediately (Tuittila et al, 1999;Zeng & Gao, 2016;Cui et al, 2017). This happens because rewetting reduces the diffusive oxygen supply in the peatland, thereby creating an anaerobic environment, which in turn inhibits the organic matter and the litter decomposition, resulting in soil organic matter accumulation and the formation of peat layer (partially decomposed organic matter) (Herbst et al, 2011;Kim et al, 2011).…”
Section: Cluster #2mentioning
confidence: 99%
“…Several studies observed that rewetting of drained peatland stimulates CO 2 -C sink functions immediately (Tuittila et al, 1999;Zeng & Gao, 2016;Cui et al, 2017). This is because rewetting reduces the diffusive oxygen supply in the peatland, thereby creating an anaerobic environment, which inturns, inhibits the organic matter and the litter decomposition resulting in soil organic matter accumulation and the formation of peat layer (partially decomposed organic matter) (Kim et al 2011;Herbst et al, 2011).…”
Section: Publication Trend Of Rdp Researchmentioning
confidence: 99%